2017
DOI: 10.1007/s40261-017-0568-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Tazarotene 0.1% Plus Clindamycin 1% Gel Versus Adapalene 0.1% Plus Clindamycin 1% Gel in Facial Acne Vulgaris: A Randomized, Controlled Clinical Trial

Abstract: ClinicalTrials.gov Identifier: NCT02721173.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…16 The main pharmacological effects of tazarotene are normalized cell differentiation, reduced hyperkeratosis, reversal of excessive proliferation, and anti-inflammatory effects on keratinocytes. 9,[17][18][19][20] Clindamycin phosphate, a commonly used drug for local treatment of acne vulgaris, has no activity in vitro and is hydrolyzed to clindamycin by phospholipase in vivo to become an active substance. 21 The antibacterial mechanism of clindamycin is that it acts on the 50S subunit of bacteria, inhibits peptide chain lengthening, and affects protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The main pharmacological effects of tazarotene are normalized cell differentiation, reduced hyperkeratosis, reversal of excessive proliferation, and anti-inflammatory effects on keratinocytes. 9,[17][18][19][20] Clindamycin phosphate, a commonly used drug for local treatment of acne vulgaris, has no activity in vitro and is hydrolyzed to clindamycin by phospholipase in vivo to become an active substance. 21 The antibacterial mechanism of clindamycin is that it acts on the 50S subunit of bacteria, inhibits peptide chain lengthening, and affects protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It also exhibits excellent pharmacokinetic characteristics in many types of diseases. 8 Numerous trials have shown that the combination of tazarotene and clindamycin is more effective than tazarotene alone, [9][10][11] but the pharmacokinetics of tazarotene with clindamycin have not been reported.…”
mentioning
confidence: 99%
“…Patients aged between 12 and 30 years, suffering from mild (Global Acne Grading System [GAGS], 1-18) to moderate (GAGS, [19][20][21][22][23][24][25][26][27][28][29][30] forms of AV (ICD-10-CM code: L70.0), 20 of either sex, literate in Bengali and consenting to participate, were eligible to be included. Exclusion criteria were patients with severe (GAGS, 31-38) to very severe (GAGS, 39 or higher) forms of AV, any uncontrolled systemic or psychiatric diseases or life-threatening illness (e.g., cancer, diabetes, epilepsy, severe asthma, ischemic heart diseases), a selfreported immuno-compromised state, pregnancy, puerperal and lactating women, subjects on hormonal contraceptives, steroids or non-steroidal anti-inflammatory drugs, those using oil-based cosmetics or undergoing…”
Section: Participantsmentioning
confidence: 99%
“…Comedão fechado e comedão aberto Pápulo-pustular Pápula: lesão cutânea primária, sólida (0,5 -1 cm) Pustula: lesão cutânea primária, líquida, contendo pús (0,5 -1 cm) 36 ainda indisponível na Europa. 11 A concentração 0,1% é a única aprovada pela FDA, sendo a espuma adequada na acne moderada a severa em idade superior a 12 anos.…”
Section: Comedónicaunclassified